Stress profiling of longevity mutants identifies Afg3 as a mitochondrial determinant of cytoplasmic mRNA translation and aging. Issue 1 (25th December 2012) - Delaney, Joe R.; Ahmed, Umema; Chou, Annie; Sim, Sylvia; Carr, Daniel; Murakami, Christopher J.; Schleit, Jennifer; Sutphin, George L.; An, Elroy H.; Castanza, Anthony; Fletcher, Marissa; Higgins, Sean; et al.
Summary Although environmental stress likely plays a significant role in promoting aging, the relationship remains poorly understood. To characterize this interaction in a more comprehensive manner, we examined the stress response profiles for 46 long‐lived yeast mutant strains across four different stress conditions (oxidative, ER, DNA damage, and thermal), grouping genes based on their associated stress response profiles. Unexpectedly, cells lacking the mitochondrial AAA protease gene AFG3 clustered strongly with long‐lived strains lacking cytosolic ribosomal proteins of the large subunit. Similar to these ribosomal protein mutants, afg3Δ cells show reduced cytoplasmic mRNA translation, enhanced resistance to tunicamycin that is independent of the ER unfolded protein response, and Sir2‐independent but Gcn4‐dependent lifespan extension. These data demonstrate an unexpected link between a mitochondrial protease, cytoplasmic mRNA translation, and aging.